Prognostic impact of new‐onset atrial fibrillation in myocardial infarction with and without improved ejection fraction - Jiachen Luo; Xiaoming Qin; Xingxu Zhang; Yiwei Zhang; Yuan Fang; Wentao Shi; Baoxin Liu; Yidong Wei; the NOAFCAMI‐SH Registry Investigators (ESC Heart Failure)
Abstract Aims Improvement in left ventricular ejection fraction (impEF) often presents in contemporary acute myocardial infarction (AMI) patients. New‐onset atrial fibrillation (NOAF) during AMI is an important predictor of subsequential heart failure (HF), while its impact on the trajectory of post‐MI left ventricular ejection fraction (LVEF) and prognostic implication in patients with and without impEF remains undetermined. We aimed to investigate the prognostic impacts of NOAF in AMI patients with and without impEF. Methods and results Consecutive AMI patients without a prior history of AF between February 2014 and March 2018 with baseline LVEF ≤ 40% and had ≥1 LVEF measurement after baseline were included. ImpEF was defined as a baseline LVEF ≤ 40% and a re‐evaluation showed both LVEF > 40% and an absolute increase of LVEF ≥ 10%. Persistently reduced EF (prEF) was defined as the second measurement of LVEF either ≤40% or an absolute increase of LVEF < 10%. The primary endpoint was a major adverse cardiac event (MACE) that was composed of cardiovascular death and HF hospitalization. Cox regression analysis and competing risk analysis were performed to assess the association of post‐MI NOAF with MACE. Among 293 patients (mean age: 66.6 ± 11.3 years, 79.2% of males), 145 (49.5%) had impEF and 67 (22.9%) developed NOAF. Higher heart rate (odds ratio [OR]: 0.84, 95% confidence interval [CI]: 0.73–0.97; P = 0.015), prior MI (OR: 0.25, 95% CI: 0.09–0.69; P = 0.008), and STEMI (OR: 0.40, 95% CI: 0.21–0.77; P = 0.006) were independent predictors of post‐MI impEF. Within up to 5 years of follow‐up, there were 22 (15.2%) and 53 (35.8%) MACE in patients with impEF and prEF, respectively. NOAF was an independent predictor of MACE in patients with impEF (hazard ratio [HR]: 7.34, 95% CI: 2.49–21.59; P < 0.001) but not in those with prEF (HR: 0.78, 95% CI: 0.39–1.55; P = 0.483) after multivariable adjustment. Similar results were obtained when accounting for the competing risk of all‐cause death (subdistribution HR and 95% CIs in impEF and prEF were 6.47 [2.32–18.09] and 0.79 [0.39–1.61], respectively). Conclusions The NOAF was associated with an increased risk of cardiovascular outcomes in AMI patients with impEF.